Rupiah Exchange Rate Reaction to Macroeconomic News Using Daily Data For 2015-2022 - Alamsyah, Rizki; Andrian, Thomas; Awaluddin, Imam (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to analyze the influence of domestic good news variables, domestic bad news, foreign good news, and foreign bad news on the rupiah exchange rate. The analysis used was using the Ordinary Least Squares method. This study added the use of lag elements and also added autoregressiveness. In the overall sample period, partial domestic bad news, foreign bad news, and changes in exchange rates had a significant positive effect on changes in the rupiah exchange rate. Meanwhile, domestic good news and foreign good news do not have a significant negative effect on changes in the rupiah exchange rate. In the period before Covid-19, partial domestic bad news and changes in the exchange rate had a significant positive effect on changes in the rupiah exchange rate. Meanwhile, bad news abroad does not have a significant positive effect on changes in the rupiah exchange rate. Domestic good news and foreign good news do not have a significant negative effect on changes in the rupiah exchange rate. In the period during Covid-19, partial domestic bad news, foreign bad news, and changes in exchange rates had a significant positive impact on changes in the rupiah exchange rate. Meanwhile, domestic good news and foreign good news do not have a significant negative effect on changes in the rupiah exchange rate. Taken together, independent variables have a significant effect on changes in the rupiah exchange rate throughout the observation period.